Research communities from the optics of University Research (Revista Electrónica REDINE, 2024)
The purpose of this essay is to analyze research communities from the perspective of university research action for intellectual production through the study of the managerial challenges of these communities from the educational, social and political point of view, considering that the university sector It is the engine that generates knowledge and drives the economy as an important part of social development. This article highlights the analysis of university research management (GIU), as a promoter of knowledge and the importance of research communities in the context of Venezuelan university education, all with the aim of strengthening the capacity that the university has. human to generate new knowledge, through the creation of research communities in university institutions it is expected to transform the way of managing knowledge through research communities in the university educational field. These trends are expected to improve and strengthen the development of knowledge through research, as a training phenomenon supported by group participation.
Keywords: Management of university research; learning communities; research strategy